Economic impact of pharmacist interventions on correction of stress-related mucosal damage prophylaxis practice - Mahmoudi L; Mohammadi R; Niknam R (Dove Medical Press, 2019)
Laleh Mahmoudi,1 Rahim Mohammadi,1 Ramin Niknam2 1Department of Clinical Pharmacy, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 2Gastroenterohepatology Research Center, Shiraz University of Medical Sciences, Shiraz, Iran Introduction: Stress-related mucosal damage (SRMD) is described as the damage of gastric mucosa due to physiological stress that is a very common complication in critically ill patients. SRMD prophylactic medications are widely prescribed all over the world, while numerous studies have revealed that a large percentage of patients admitted to non-intensive care unit (ICU) services do not need to receive these medications. The aim of this study was to determine the frequency and type of medication errors and the economic impact of clinical pharmacist intervention on stress ulcer prophylaxis (SUP).Methods: This prospective interventional study was conducted on adult patients admitted to internal, surgical, and critical care units at two large academic medical centers over 6 months. Risk factors of stress ulcer were recorded daily during hospital stay, and appropriateness of SUP administration was assessed according to the American Society of Health-System Pharmacists (ASHP) criteria. An intervention was performed by a clinical pharmacist in the case of contradictions. The rate of inappropriate SUP and the economic impact of a pharmacist intervention were recorded.Results: In this study, 178 out of 219 (81.2%) patients received prophylactic treatments. Averagely, prophylactic therapy was compatible with standard treatment guidelines in 67.1% of cases. The implementation of ASHP guideline by a clinical pharmacist resulted in a cost saving of >18,000 USD monthly in this study, which would result in an estimated cost saving of >216,000 USD annually.Conclusion: Although treatment guidelines are available for the prophylaxis of SRMD, failure to observe these guidelines could increase the cost of treatment and adverse effects. The clinical pharmacists’ intervention in order to implement standard protocols has a significant impact on the reduction of unintended mistakes in prescribing prophylaxis, as well as significant cost savings. Keywords: acid suppression therapy, clinical pharmacy, histamine-2 receptor antagonist, proton pump inhibitor, stress ulcer prophylaxis